Notes on Indian Grasses-IV. The Identity and Distribution of Certain Species - Jain, S. K. (Indian Forester, 1968)
The identity and distribution of seven grasses, namely, Bothriochloa pseudoischaemum (Nees) Henr., Cenehrus echinatus Linn., Coelorhachis glandulosa (Trin.) Stapf, Festuca undata Stapf var. aristata Stapf, Ischaemum impressum Hack., Poa litwinowiana Ovcz. And Stipa purpurea Griseb. Are discussed. Coelorhachis glandulosa (Trin.) Stapf is being reported from India for the first time.